1988
DOI: 10.1159/000261078
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Timing of Fluoride Treatment on Enamel De- and Remineralization in vitro: A pH-Cycling Study

Abstract: An in vitro pH-cycling experiment was completed to determine the effect of the timing of fluoride toothpaste application on de- and remineralization. Both initially sound enamel and artificially produced enamel lesions were subjected to a pH-cycling scheme. The lesions were either formed in an undersaturated calcium-phosphate-fluoride-acetate system (CPF lesions) or in a MHDP-containing lactate buffer (MHDP lesions). The two systems produced subsurface demineralization which differed in porosity, depth and sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1
2

Year Published

1990
1990
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 8 publications
0
19
1
2
Order By: Relevance
“…The use of SH loss to evaluate enamel-dentin demineralization is supported by the available literature. 8,20 Although our results contradict those found by ten Cate et al, 1 these authors used an in vitro design, which may account for the observed differences compared to our in situ study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The use of SH loss to evaluate enamel-dentin demineralization is supported by the available literature. 8,20 Although our results contradict those found by ten Cate et al, 1 these authors used an in vitro design, which may account for the observed differences compared to our in situ study.…”
Section: Discussioncontrasting
confidence: 99%
“…Although F toothpaste is able to provide F ions to the oral cavity to interfere with both phenomena, 4,5 its effect when used before or after demineralizing challenges has only been studied in vitro. 1 In this in vitro study, 1 no difference was observed between F toothpaste used to inhibit the demineralization process or to enhance the mineral repair that occurs during the subsequent remineralization. However, the effect of the timing of brushing with F toothpaste has not been studied under conditions that simulate clinical F use, and the effect of this timing on root dentin demineralization is completely unknown.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Sections in groups B, C, D, E, F and G were immersed for 5 min every day in neutral sodium fluoride solutions containing 1, 250, 500, 1,000, 1,750 and 2,500 ppm fluoride, respectively. In this study, treatment with the fluoride solution was always carried out immediately after the demineralizing cycle although it has been shown [ten Cate et al, 1988] that inhibition of lesion progression will be observed irre spective of the timing of the fluoride therapy. The demineralizing and artificial saliva solutions were regularly analysed for fluoride; the levels were always found to be below 0.03 ppm.…”
Section: Methodsmentioning
confidence: 99%
“…Sev eral different versions of the pH-cycling technique have been described [ten Cate and Duijsters, 1982;Featherstone et al, 1986Featherstone et al, , 1988Gcrrard and Winter, 1986;White, 1987;Damato et al, 1988;ten Cate et al. 1988;White, 1988].…”
Section: Introductionmentioning
confidence: 99%